AKUNTABILITAS PELAKSANAAN PROGRAM GERAKAN TERPADU KESEHATAN EKONOMI PENDIDIKAN INFRASTRUKTUR DAN LINGKUNGAN (GERDU KEMPLING) TAHUN 2011-2014 DI KECAMATAN SEMARANG BARAT - Anggie Desta Ervita; Titik Djumiarti (Journal of Public Policy and Management Review, 2017)
This research was to identify and describe the factors to increase the accountability of program implementation Gerdu Kempling on 2011-2014 in the Districts of West Semarang and analyzes the accountability of implementation program Gerdu Kempling on 2011-2014 in the Districts of West Semarang. This research is a qualitative descriptive study by collecting data through interview and document study. Informants were collected from District of West Semarang, Village Gisikdrono and Village Kalibanteng Kulon. In this study, researcher used the factors for successful accountability and dimensions of accountability. The results obtained is still not optimal. It is known through research that show the factors to increase the accountability that is an exemplary leader, openness and clarity of information, legitimacy and recognition and feedback has been good, but to increase coordination in the delivery of mail is still not good enough and the communication process is too simple. In addition to the dimensions of accountability shows that the policy of accountability and program accountability is still not optimal. The advices given by the researcher is about to improve exemplary leader to participate in the promotion phase and training, coordination by integrating Programme activities Gerdu Kempling, provision of information services on the website, Development with marketing, improvement of human resources with the ESQ training, Gathering and Outbound, Preparation action program through Participatory Learning and Action (PLA), improved performance division of labor based on the ability of the executive team programs Gerdu Kempling, preparation of the integrity zone with the team programs Gerdu Kempling, preparation of technical monitoring periodically in accordance with technical guidelines that have been set.